Does Preoperative Halo-Gravity Traction Reduce the Degree of Deformity and Improve Pulmonary Function in Severe Scoliosis Patients With Pulmonary Insufficiency? A Systematic Review and Meta-Analysis - Yang, Zhao; Liu, Yang; Qi, Longtao; Wu, Shanshan; Li, Jingwen; Wang, Yu; Jiang, Bin (Frontiers in Medicine, 2021)
Abstract Background Halo-gravity traction is a commonly used clinical intervention to reduce surgical risk in patients with scoliosis before surgical correction. Some previous studies have focused on the application of halo-gravity traction on patients with severe spinal deformity and pulmonary insufficiency, but the overall effect of halo-gravity traction has not been fully understood. The object of the present study was to perform a meta-analysis exploring the efficacy of preoperative halo-gravity traction on radiographic measurement and pulmonary function in severe scoliosis patients with pulmonary insufficiency. Methods We searched the medical literatures completed before January 17th, 2021 in the databases of Pubmed, Embase and Cochrane Library. Studies analyzed the effects of halo-gravity traction on severe scoliosis patients’ deformity and pulmonary functions quantitatively were included. Two researchers independently conducted the literature search, data extraction and quality assessment. We used the Review Manager Software (version 5.4) for statistical analysis and data analysis. Mean difference (MD) with 95% confidence intervals (CIs) were calculated to evaluate the effects of halo-gravity traction. Results Seven studies involving 189 patients received halo-gravity traction therapy preoperatively were analyzed in our study. Preoperative halo-gravity traction significantly ameliorated the degree of deformity in severe scoliosis patients with pulmonary insufficiency, especially reduced coronal Cobb angle and sagittal Cobb angle effectively (MD=27.28 [95%CI 21.16 to 33.40], p<0.001; MD=22.02 [95%CI 16.80 to 27.23], p<0.001). Preoperative halo-gravity traction also improved the pulmonary functions in patients, especially increasing %FVC and %FEV1 (MD=-0.0662 [95%CI -0.0672 to -0.0652], p<0.001; MD=-0.0824 [95%CI -0.0832 to -0.0816], p<0.001). Conclusions Preoperative halo-gravity traction for severe scoliosis patients shows significant improvement in degree of deformity and pulmonary functions. Halo-gravity traction is an effective method to improve patients’ tolerance to surgery in perioperative period.